2017
DOI: 10.1177/1090198117709316
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Media Doses of the Tips From Former Smokers Campaign and Cessation Behaviors and Intentions to Quit Among Cigarette Smokers, 2012-2015

Abstract: The Tips campaign has had a substantial impact on cessation behaviors among U.S. adult smokers over time. These data support the continued use of graphic and/or emotional media campaigns that encourage smokers to quit to further reduce tobacco use in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 36 publications
(77 reference statements)
5
62
0
2
Order By: Relevance
“…These data add to the body of research demonstrating that state and national tobacco education campaigns are effective. This study supports the conclusions of other effective campaigns, 17,18 specifically that high levels of extended advertising are required for media campaigns to achieve sustainable population changes in smoking behavior. Demonstrating the effects of digital and TV media on population-level behavior for youth requires longitudinal studies with sufficient sample sizes, which can be costly.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These data add to the body of research demonstrating that state and national tobacco education campaigns are effective. This study supports the conclusions of other effective campaigns, 17,18 specifically that high levels of extended advertising are required for media campaigns to achieve sustainable population changes in smoking behavior. Demonstrating the effects of digital and TV media on population-level behavior for youth requires longitudinal studies with sufficient sample sizes, which can be costly.…”
Section: Discussionsupporting
confidence: 85%
“…Models controlled for confounding influences, similar to other longitudinal media studies. 15,18,20,26 The risk for smoking initiation for each youth in the sample who reported never smoking at baseline was assessed as they aged during the study period. Once the event of interest (smoking initiation) occurred, the youth was dropped from subsequent time periods and the probability that a youth-initiated smoking at each age was calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de terem um alto custo, são eficazes para a redução do hábito de fumar e para o fortalecimento de políticas públicas como proibição do fumo em locais fechados, o que diminui também o fumo passivo. 47,48 Dentre os fatores limitantes deste estudo, destacam-se a ausência de artigos provenientes de países de baixa renda, a inclusão de artigos apenas em inglês, português e espanhol e a exclusão de teses e dissertações.…”
Section: Discussionunclassified
“…Research shows that mass media campaigns can effectively encourage smoking cessation and contribute to reductions in smoking prevalence among adults aged 18 or older (1)(2)(3)(4). An international review of evidence from 121 anti-tobacco mass media campaigns showed strong evidence of positive behavioral effects (5).…”
Section: Introductionmentioning
confidence: 99%
“…An international review of evidence from 121 anti-tobacco mass media campaigns showed strong evidence of positive behavioral effects (5). However, increases in population-level quit attempts have been shown to fade shortly after a campaign ends (1). A national tobacco education campaign for adults, the Centers for Disease Control and Prevention's (CDC's) Tips From Former Smokers (Tips), has aired intermittently since 2012.…”
Section: Introductionmentioning
confidence: 99%